The Significance of Brand Positioning to UX Design Business Growth - Ferdian, Bayu Bagja (Penerbit Goodwood, 2024)
Purpose: This paper illustrates the significant branding enhancement for PT Laluasa Cipta Asia using the concept of brand positioning strategy, specifically for one of their business units called Gizalab which focuses on User Experience design services. The study's primary objective was to evaluate the current service process to identify strengths and weaknesses, understand customer behavior, and analyze the competitive landscape. Method: The main methods in this study are market surveys, competitor analysis, and in-depth interviews. The author uses a market survey to discover how the target market perceived the existing brand perception. This understanding is important as the basis for the creative brand positioning strategy. Results: While VRIO analysis emphasizes what valuable resources are from the company’s point of view, the in-depth interviews exhibit the gap in what matters to the customers and the target market. There are several key prominent insights found through in-depth interviews, one of them is the poor performance of the company’s branding strategies. The research results indicate that the existing Gizalab’s branding as the user experience design expert is not perceived as intended and currently is not convincing the target market. Conclusions: The study highlights the critical importance of basic branding elements in supporting business growth and stakeholder vision. A key finding reveals that Gizalab lacks foundational branding assets, particularly a clear brand positioning. Without a strong and concise positioning statement, the company risks confusing potential clients and missing opportunities for differentiation in the market. Limitations: This study was limited to an internal branding assessment and did not include comprehensive market analysis or competitor benchmarking, which could provide a deeper context for strategic positioning. Contributions: The findings of this study are particularly relevant to branding consultants, marketing strategists, and business development teams working with startups or SMEs lacking structured brand frameworks.